1979
DOI: 10.1002/ar.1091930105
|View full text |Cite
|
Sign up to set email alerts
|

Ultrastructural cytochemistry of atrial muscle cells. VI. Comparative study of specific granules in right and left atrium of various animal species

Abstract: Specific (A-, B-and D-) granules as well as multivesicular bodies (MVB) with a dense core from the right and left atrium of a variety of mammals (mouse, rat, hamster, guinea pig, rabbit, young and old cat) were compared by quantitative ultrastructural and cytochemical methods as regards number, size, localization and reactivity. The number of specific granules was greater in the right atrium of the rat and lesser in the same atrium of the guinea pig. In the rat this difference was due t o a greater number of a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
37
0
2

Year Published

1984
1984
2004
2004

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 64 publications
(42 citation statements)
references
References 31 publications
3
37
0
2
Order By: Relevance
“…On the other hand, the distribution pattern of granules was common to all species examined in that the granules were more frequently observed in the perinuclear region than between myof ibrillar bundles. These cellular distributions of ANP-granules were consistent with those in the previous reports [2,7].…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…On the other hand, the distribution pattern of granules was common to all species examined in that the granules were more frequently observed in the perinuclear region than between myof ibrillar bundles. These cellular distributions of ANP-granules were consistent with those in the previous reports [2,7].…”
Section: Discussionsupporting
confidence: 93%
“…Using morphometry, the size and number of ANP-granules were examined in various mammalian species by Jamieson and Palade [9], Tomisawa [28], and Cantin et al [2].…”
mentioning
confidence: 99%
“…Ultrastructural morphometry: The number of secretory granules of the right auricular cardiocytes was measured according to the modified morphometry method of Cantin et al [6]. Thin sections were viewed on a JEM-2000 EX electron microscope at a magnification of × 3,000.…”
Section: Immunohistochemistrymentioning
confidence: 99%
“…Thin sections were viewed on a JEM-2000 EX electron microscope at a magnification of × 3,000. Ten photographs were randomly chosen from sections of the right auricular cardiocytes of each mouse in accordance with the criteria proposed by Cantin et al [6]. The counting of ANP-granules was done on 25 cm × 30 cm prints at a final magnification of × 14,000, corresponding to an area of 382.7 µm 2 .…”
Section: Immunohistochemistrymentioning
confidence: 99%
“…Concerning the number of atrial secretory granules, Cantin et al [3] have reported on various mammals, and they described that the average total number of ANP-granules in the right atrium of the rat was 103.84, and of the hamster was 48.84. They commented that the total number of ANP-granules in atria decreased with increasing size of the animals.…”
mentioning
confidence: 99%